Evaluasi Keamaan Sistem Informasi pada Dinas Pendidikan dan Kebudayaan Kota Balikpapan Menggunakan Indeks KAMI 5.0 - Rara Krisna Adi Susilo; Dwi Arief Prambudi (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
The Balikpapan City Education and Culture Office is a regional government tasked with managing, developing, and advancing the fields of education and culture in accordance with Government Regulation Number 19 of 2005 concerning National Education Standards. Documents managed by the Balikpapan City Education and Culture Office include personal data of students and parents, personal data of teachers, and data from various schools in Balikpapan City. The security of these documents must be maintained to protect public privacy and comply with PDP Law Number 27 of 2022 concerning the protection of personal data. Based on the interview results, the Balikpapan City Education and Culture Office has never conducted an evaluation of information security either internally or externally through the National Cyber and Crypto Agency (BSSN). The use of the KAMI Index acts as an assessment tool that assesses every aspect of the KAMI Index 5.0 with the ISO/IEC 27001:2022 standard. At this research stage, an assessment of the SE Category, an assessment of the KAMI Index area, analysis and discussion of the results, and recommendations for improvement were carried out. From the evaluation results, the Electronic System Category value was obtained as 42 and the Evaluation Results showed the status of "Not Eligible" with a value of the level of completeness of information security of 264. There are 129 recommendations for improvement provided and are expected to help the Balikpapan City Education and Culture Office in identifying various threats and vulnerabilities that can affect information security in providing procedures and reducing the risks that have been identified.